THE CONTRIBUTION OF HUMANITARIAN AFFAIRS ASIA ON MAINSTREAMING HUMAN SECURITY ISSUES IN ASIA - Richo Bimapaksi Jumranuddin (HI 16 UMY 057, 2016)
*57 This undergraduate thesis will analyze the strategy of Humanitarian Affairs Asia on mainstreaming human security through their activities. However, we have to understand first what is the mainstreaming itself in term of human security. According to Wolfgang Benedek, Matthias C. Kettemann, and Markus M. their book with title Mainstreaming Human Security in Peace Operations and Crisis Management: Policies, Problems, Potential, non-state actors (non-governmental organizations) has an important role in mainstreaming human security issues. Non-governmental organization must provide information and help increased awareness on human security issues. Non-governmental organizations also important to gather and publish the information, and bring people from different backgrounds to approaches and mainstreaming human security issues.